Screening and function analysis of functional Monascus strains in high-temperature Daqu - ZHNAG Zhu, HUANG Jun, ZHOU Rongqing, LEI Zilun, TANG Qiuxiang, WAN Yingdong, ZHANG Suyi, QIN Hui, DONG Yi, WANG Chao, WANG Xiaojun, RAN Maofang (Zhongguo niangzao)
In this study, Monascus strains were screened from high-temperature Daqu with the pink color through the cultured technology. By combining multivariate statistical analysis methods, the metabolic characteristics of these strains in pure cultured wheat Qu, simulated Baijiu solid-state fermentation and fortified Daqu were studied. Subsequently, excellent functional Monascus strains were screened. The screened strains were identified by morphological observation and molecular biology techniques. The results showed that three excellent functional Monascus strains were isolated and screened, numbered as H14, H26 and H30. Among them, strain H14 showed potential ability to increase the base liquor yield (7.5%vol) and improving the profile of volatile compounds and their contents (33.12 mg/kg) in fermented grains. Strain H30 improved the esterification activity of high-temperature Daqu, and strain H26 demonstrated the potential to produce characteristic flavor compounds (pyrazines), with a content of 0.27 mg/kg for 2,3,5,6-tetramethylpyridine in high temperature fortified Daqu. Through identification, strains H14, H26, and H30 were all identified as Monascus floridanus.